(untitled) (Journal of Universal Science Research, 2025)
Patterns play a significant role in modern architecture, enhancing aesthetics, functionality, and sustainability. From decorative façades to energy- efficient structures, patterns contribute to both design and performance. This article explores various solutions for integrating patterns into contemporary buildings effectively.